STUDI KUALITATIF : DAMPAK KEBIJAKAN INSENTIF PAJAK USAHA KECIL DAN MENENGAH TERHADAP KEPATUHAN PAJAK DAN PENERIMAAN NEGARA - Khairiyah, Yotasa Raidah; Akhmadi, Muhammad Heru (Politeknik Keuangan Negara STAN, 2019)
Government Regulation Number 23 of 2018 is a form of tax incentives given by the government to tax payers for Micro, Small and Medium Enterprises (MSMEs). The regulations aim at realizing fair taxation and increasing state revenue. Data from the Ministry of UKM shows that the number of MSMEs in Indonesia until 2018 is 64,194,057 units and absorbs 107,376,540 people. This study examines the compliance of SMEs in paying taxes before and after the enactment of tax incentives. Using a qualitative approach, this study seeks to explain the impact of incentive policies on MSME taxpayer compliance and state revenue. Respondents were observed in the South of Tangerang city area with interview techniques. The results of the study showed that in terms of compliance, statistically 2016-2018 showed an increase in registered taxpayers, but the SMEs did not voluntarily pay taxes because they felt they had not benefited directly. In addition, the ability to keep books is still limited. This has an impact on the side of state revenue, which is still low tax revenue from the MSME sector when compared to taxation revenues from other sectors